2013
DOI: 10.1111/fwb.12172
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of competition between two bloom‐forming Microcystis species

Abstract: Summary Cyanobacteria, a phylum of bacteria that obtains energy by oxygenic photosynthesis, can be found in almost every terrestrial and aquatic habitat on Earth and play an important role in global carbon and oxygen cycles and as food sources for fish. However, common bloom‐forming cyanobacteria in the genus Microcystis produce microcystins that are toxic to human beings and aquatic animals and can have disastrous effects in aquatic ecosystems. Algal species follow seasonal successions of bloom formation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 30 publications
(38 reference statements)
0
16
0
1
Order By: Relevance
“…However, Imai et al (2009a, b) reported much higher growth of M. aeruginosa than M. wesenbergii at high temperature (30 and 35°C), but similar growth rates of the two species at low temperature (20 and 25°C). Zhai et al (2013) found higher growth of M. aeruginosa (FACBH 905) than M. flos-aquae (FAHCB 1028) at 25°C. The results of both studies contradict our present results.…”
Section: Discussionmentioning
confidence: 91%
“…However, Imai et al (2009a, b) reported much higher growth of M. aeruginosa than M. wesenbergii at high temperature (30 and 35°C), but similar growth rates of the two species at low temperature (20 and 25°C). Zhai et al (2013) found higher growth of M. aeruginosa (FACBH 905) than M. flos-aquae (FAHCB 1028) at 25°C. The results of both studies contradict our present results.…”
Section: Discussionmentioning
confidence: 91%
“…M. wesenbergii was also significantly correlated with TN, TP and WT, indicating that the dynamic of M. wesenbergii was probably influenced extensively by both nutrients (nitrogen and phosphorus) and temperature. Previous studies have demonstrated that the WT had significant influence on the growth and succession of Microcystis species (Krüger and Eloff, 1978;Imai et al, 2009;Zhai, 2013). Imai et al (2009) Lake Kasumigaura, Japan.…”
Section: Explanation Of the Dynamics Of Microcystis Morphospeciesmentioning
confidence: 99%
“…has extended its coverage and persistence throughout the summer (Guo 2007;Deng et al 2014;Qin et al 2007), similar to other shallow lakes in the world, such as Lake Okeechobee (USA) (James et al 2009) and Lake Engelsholm (Denmark) (Søndergaard et al 2013). In order to understand and control the eutrophication, some studies have been performed in Taihu, mainly focused on three aspects: (1) the physical and chemical changes in the water body and sediment (Han et al 2013;Liu et al 2013); (2) the algal community and algal toxin production changes Zhai et al 2013); (3) the microbial community changes in water body and sediment (Chen et al 2008;Hou et al 2013a;Shao et al 2013;Wu et al 2007;Ye et al 2009), which showed vertical variation of bacterial community (Ye et al 2009) and significant seasonal variation in February and August in sediment (Shao et al 2011). However, further study on the microbial communities by the molecular methods, in coupling with the physicochemical characterization of water and sediment could enable a better understanding about the interactions among the environment factors, the prokaryotic communities and the algal bloom.…”
Section: Introductionmentioning
confidence: 99%